To solve the system of equations using elimination, we start with the two given equations:
- \( 4x - 6y = -48 \) \quad (Equation 1)
- \( -2x + 4y = 30 \) \quad (Equation 2)
Step 1: Multiply the equations to align the coefficients for elimination.
To eliminate \(x\), we can manipulate the equations such that their coefficients are opposites. We can multiply Equation 2 by 2:
\[ 2 \times (-2x + 4y) = 2 \times 30 \]
This gives us:
\[ -4x + 8y = 60 \quad (Equation 3) \]
Step 2: Now, we can add Equation 1 and Equation 3.
The updated equations are:
- \( 4x - 6y = -48 \)
- \( -4x + 8y = 60 \)
Now, we add both equations:
\[ (4x - 6y) + (-4x + 8y) = -48 + 60 \]
This simplifies to:
\[ 0x + 2y = 12 \]
So, we have:
\[ 2y = 12 \]
Step 3: Solve for \(y\).
Dividing both sides by 2, we get:
\[ y = 6 \]
Step 4: Substitute \(y\) back into one of the original equations to solve for \(x\).
We can use Equation 1:
\[ 4x - 6(6) = -48 \]
This simplifies to:
\[ 4x - 36 = -48 \]
Adding 36 to both sides gives:
\[ 4x = -48 + 36 \] \[ 4x = -12 \]
Now we divide by 4:
\[ x = -3 \]
Step 5: Solution
The solution to the system of equations is:
\[ \boxed{( -3, 6 )} \]
Verification
Let's verify by substituting \(x = -3\) and \(y = 6\) back into the original equations:
-
Substituting into Equation 1: \[ 4(-3) - 6(6) = -12 - 36 = -48 \quad \text{(True)} \]
-
Substituting into Equation 2: \[ -2(-3) + 4(6) = 6 + 24 = 30 \quad \text{(True)} \]
Both equations check out, confirming that the solution \( ( -3, 6 ) \) is correct.